Thomas Aquinas’ influences inInfanteD. Pedro’ “Virtuosa Benfeitoria”: Scholastic tradition in History and History of Education - Terezinha Oliveira (Acta Scientiarum. Education, 2016)
The considerations on the book “VirtuosaBenfeitoria” aim atevaluating the relevance of a social project to guide the actions of the ruler and theindividuals, with a view to practical actions that converge to the common good. The infant D. Pedro, also known as the Duke of Coimbra, wrote the work. The central focus of the book is to address the sense of improvement and how the prince should practice and bestow it and how the subjects would receive and practice it. The arguments of D. Pedro to deal with the good and the society are strongly influenced by classical authorities and authors of scholasticism, especially Thomas Aquinas. In this sense, on the one hand our study seeks to show that such knowledge was essential for him to understand the plots that build human relationships, whose premises, to him, should be the ones leading society towards the common good;on the other hand, the goal is to analyze the work we regard as essential theoretical and methodological principles of history that allow us to recover, through memory, historical events that potentially guide us through paths that show the relevance of the Master of the University, as a vector in the organization of a given society.